Salt-added method for breaking azeotrope of binary IPA-water system : using aspen plus - Shahidatul Nadiah, Mhd Said (2008)
Distillation process is a method for separating various components of a liquid solution depending upon the distribution of these components between a vapour phase and a liquid phase. It is commonly used as a solvent recovery method, a technology in many areas of pharmaceutical and especially chemical industries. IPA is a rubbing alcohol used as cleaner and solvent in industries. It forms azeotrope with water that ordinary distillation can never separate both components directly. Mostly in industries, azeotropy and highly nonideal behavior during distillation complicates the recovery of solvents and the not recovered solvents usually end up as toxic waste. Apart from that, the interest of this project is to study the azeotrope breaking of binary IPA-water system with salt-added method to recover purity of IPA by using batch distillation in the Aspen Plus environment. Then, the concentration of salt added to break the azeotrope of IPA-water system in batch distillation process is investigated. After coming up with a simulation solution based on the optimum condition of chosen parameters, the result show that the azeotrope breaking of binary IPA-Water system with salt added method is not successful by using batch distillation via simulation of Aspen Plus. The azeotropic point of the binary IPA-Water system has only shifted but failed to break. Thus, it is recommended to do an experimental of the batch distillation in order to understand more of the salt-added method in breaking the azeotope system and then to implement the same method in simulation to achieve the objective.